Answer:The solutions are -3 and -6
Explanation:First we would need to put the equation in standard form which is:
ax² + bx + c = 0
This can be done as follows:
x² + 18 = -9x
x² + 9x + 18 = 0
By comparison, we would find that:
a = 1
b = 9
c = 18
Now, to get the roots, we would use the quadratic formula shown in the attached image.
By substitution, we would find that:
either x =
![\frac{-9+ \sqrt{(9)^2-4(1)(18)} }{2(1)} = -3](https://tex.z-dn.net/?f=%20%5Cfrac%7B-9%2B%20%5Csqrt%7B%289%29%5E2-4%281%29%2818%29%7D%20%7D%7B2%281%29%7D%20%3D%20-3)
or x =
![\frac{-9- \sqrt{(9)^2-4(1)(18)} }{2(1)} = -6](https://tex.z-dn.net/?f=%20%5Cfrac%7B-9-%20%5Csqrt%7B%289%29%5E2-4%281%29%2818%29%7D%20%7D%7B2%281%29%7D%20%3D%20-6)
Hope this helps :)
Answer:
See attachment
Step-by-step explanation:
See attachment
1.75 is the same as 1 3/4
1.5 is halfway between 1 and 2
1/2 is halfway between 0 and 1
1/4 is a quarter between 0 and 1
Answer:
( 24 / 3 ) + x
Step-by-step explanation:
the expression would be ( 24 / 3 ) + x
Answer:
the correct graph is b for this problem
Answer:
The simplified expression is:
![\frac{2}{5}y+\frac{1}{5}x-0.2y-6+\left(-2\right)=0.2y+0.2x-8](https://tex.z-dn.net/?f=%5Cfrac%7B2%7D%7B5%7Dy%2B%5Cfrac%7B1%7D%7B5%7Dx-0.2y-6%2B%5Cleft%28-2%5Cright%29%3D0.2y%2B0.2x-8)
Step-by-step explanation:
Given the expression
![\frac{2}{5}y+\frac{1}{5}x-0.2y-6+\left(-2\right)](https://tex.z-dn.net/?f=%5Cfrac%7B2%7D%7B5%7Dy%2B%5Cfrac%7B1%7D%7B5%7Dx-0.2y-6%2B%5Cleft%28-2%5Cright%29)
![\mathrm{Remove\:parentheses}:\quad \left(-a\right)=-a](https://tex.z-dn.net/?f=%5Cmathrm%7BRemove%5C%3Aparentheses%7D%3A%5Cquad%20%5Cleft%28-a%5Cright%29%3D-a)
![=\frac{2}{5}y+\frac{1}{5}x-0.2y-6-2](https://tex.z-dn.net/?f=%3D%5Cfrac%7B2%7D%7B5%7Dy%2B%5Cfrac%7B1%7D%7B5%7Dx-0.2y-6-2)
![\mathrm{Group\:like\:terms}](https://tex.z-dn.net/?f=%5Cmathrm%7BGroup%5C%3Alike%5C%3Aterms%7D)
![=\frac{2}{5}y-0.2y+\frac{1}{5}x-6-2](https://tex.z-dn.net/?f=%3D%5Cfrac%7B2%7D%7B5%7Dy-0.2y%2B%5Cfrac%7B1%7D%7B5%7Dx-6-2)
Add similar elements
![=0.2y+\frac{1}{5}x-6-2](https://tex.z-dn.net/?f=%3D0.2y%2B%5Cfrac%7B1%7D%7B5%7Dx-6-2)
![=0.2y+\frac{x}{5}-6-2](https://tex.z-dn.net/?f=%3D0.2y%2B%5Cfrac%7Bx%7D%7B5%7D-6-2)
![=0.2y+\frac{x}{5}-8](https://tex.z-dn.net/?f=%3D0.2y%2B%5Cfrac%7Bx%7D%7B5%7D-8)
![=0.2y+0.2x-8](https://tex.z-dn.net/?f=%3D0.2y%2B0.2x-8)
Thus, the simplified expression is:
![\frac{2}{5}y+\frac{1}{5}x-0.2y-6+\left(-2\right)=0.2y+0.2x-8](https://tex.z-dn.net/?f=%5Cfrac%7B2%7D%7B5%7Dy%2B%5Cfrac%7B1%7D%7B5%7Dx-0.2y-6%2B%5Cleft%28-2%5Cright%29%3D0.2y%2B0.2x-8)